Persistent pharmaceutical concentrations in an urban Western Cape Estuary and the effects on microalgal assemblages - Murgatroyd, Olivia (Department of Biological Sciences, 2025)
Coastal environments comprise distinct and diverse ecosystems of economic and ecological significance that provide invaluable ecosystem functions and services to humans. Despite their significance, coastal environments worldwide are experiencing deterioration due to the growth of the human population and associated activities in coastal areas. Chemicals of emerging concern, including pharmaceuticals and personal care products, are a prominent example of an emerging threat to coastal environments due to their ubiquity and persistence in marine environments globally. However, research on levels of pharmaceutical pollution and associated effects on ecological processes and biota in estuaries is severely lacking in South Africa. Therefore, the consequences for key estuarine biota and the functions they provide are largely unknown, to the best of my knowledge. Therefore, the purpose of this study was to address the above-mentioned knowledge gaps on pharmaceutical pollution in South Africa. This aim was addressed by firstly determining the concentration of pharmaceuticals in the Zandvlei Estuary, which is an urbanized, anthropogenically manipulated system in the Western Cape, South Africa. Thereafter, the interaction between sulfamethoxazole presence and sandprawn density was quantified experimentally to understand the responses of microalgae biomass. An experiment was conducted as the consequences of pharmaceutical pollution on functionally important estuarine biota such as sandprawns and the functions they provide including biofiltration in South African estuaries are, to the best of my knowledge, unknown. Based on field sampling, high concentrations of pharmaceuticals were recorded in the Zandvlei Estuary, particularly near the mouth, where acetaminophen had the highest average concentration in water samples among all sites (4.604 ± 0.453 μg/L) and the highest average concentration in sandprawn samples (11.309 μg/g). Additionally, pharmaceuticals including sulfamethoxazole, carbamazepine and diclofenac were detected in water samples in all sites and all sandprawn samples. With the use of environmentally relevant sulfamethoxazole concentrations in a laboratory mesocosm experiment, I found that sulfamethoxazole presence negatively affected pelagic microalgae biomass, where micro- and picoplankton declined with sulfamethoxazole concentrations but nanoplankton and benthic microalgae was unaffected. The high levels of pharmaceuticals found in the Zandvlei Estuary are likely a result of increasing sewage spills due to malfunctioning sewage pump stations, which in turn is likely amplified by load shedding (planned electricity outages to manage demand) intensifying over the last seven years. Findings additionally highlight the potential for small, urban temporary-open closed estuaries to be accumulation sites for chemicals of emerging concern, given the order of magnitude greater values recorded in the Zandvlei Estuary compared to False Bay. Moreover, this study has shown that increasing sulfamethoxazole concentrations cause a reduction in phytoplankton biomass and a shift in size classes. These findings need further research to understand ecological repercussions for food web topology and efficiency, for example, given that changes in phytoplankton abundance and traits can generate indirect bottom-up changes to higher trophic levels.